My Diagnostic Odyssey—A Call to Expand Access to Genomic Testing for the Next Generation - Michelson, Jeremy (The Hastings Center report, 2018)
I attended the NSIGHT Ethics and Policy Advisory Board's meeting on sequencing newborns as a research associate in a joint apprenticeship between the University of California, San Francisco, Institute for Human Genetics and the university's Program in Bioethics. But I also came to the meeting with a deeply personal perspective: I had spent nearly my entire childhood in search of a diagnosis and therefore was eager to hear the board's discussion on how to ethically include genomic sequencing early in life. Genomic sequencing in the newborn period could have helped me avoid my diagnostic odyssey by revealing the cause of my condition shortly after birth.